"Goals for Driver Education" Model as a Guide for Safe Driving Education and Training in Algeria - Touil, Adel (2026)
This essay provides a conceptual and methodological framework based on self-assessment of safe driving skills as an educational strategy to improve the quality of road safety education in Algeria. It aims to improve and develop the current program by adopting the content of the GDE model, which has proven its effectiveness in the field of traffic safety. Its monitoring allows the implementation and evaluation of procedures, policies, and programs, particularly those that focus on high-level driving skills. In Algeria, road safety education is included in school curricula from the primary level (around six years of age) and continues through middle and secondary education, with the aim of instilling a culture of road safety and promoting positive behavior on the road. At the conceptual level, this work calls for the need to shift the concept of road safety education towards more effective and comprehensive concepts compared to current programs that rely mainly on procedural skills training.  At the methodological level, the GDE model proposes teaching driving according to a hierarchical sequence that progress from learning basic skills to high-level driving skills. It serves as a basis for designing a driving education program based on an integrated theoretical framework and scientific background, and for directing the educational process, identifying and activating relevant strategies and indicators. This should be prepared according to a scientific methodology, and is hoped to serve as an effective tool in addressing the traffic phenomenon.